Developmental errors in the common marmoset retina - Haverkamp, Silke; Mietsch, Matthias; Briggman, Kevin L. (Frontiers in Neuroanatomy, 2022)
Although retinal organization is remarkably conserved, morphological anomalies can be found to different extents and varieties across animal species with each presenting unique characteristics and patterns of displaced and misplaced neurons. One of the most widely used non-human primates in research, the common marmoset (Callithrix jaccus) could potentially also be of interest for visual research, but is unfortunately not well characterized in this regard. Therefore, the aim of our study was to provide a first time description of structural retinal layering including morphological differences and distinctive features in this species. Retinas from animals (n = 26) of both sexes and different ages were immunostained with cell specific antibodies to label a variety of bipolar, amacrine and ganglion cells. Misplaced ganglion cells with somata in the outermost part of the inner nuclear layer and rod bipolar cells with axon terminals projecting into the outer plexiform layer instead of the inner plexiform layer independent of age or sex of the animals were the most obvious findings, whereas misplaced amacrine cells and misplaced cone bipolar axon terminals occurred to a lesser extent. With this first time description of developmental retinal errors over a wide age range, we provide a basic characterization of the retinal system of the common marmosets, which can be taken into account for future studies in this and other animal species. The finding of misplaced ganglion cells and misplaced bipolar cell axon terminals was not reported before and displays an anatomic variation worthwhile for future analyzes of their physiological and functional impact.